Validation of the Malay Version of Auditory Verbal Learning Test (MVAVLT) Among Schizophrenia Patients in Hospital Universiti Sains Malaysia (HUSM), Malaysia - Jamaluddin, Ruzita; Othman, Zahiruddin; Musa, Kamarul Imran; Alwi, Muhammad Najib Muhammad (ASEAN Federation of Psychiatry and Mental Health (AFPMH), 2009)
Objective: Many studies have emphasized the significance of verbal memory for the functional outcome in schizophrenia. A preserved capability to encode and recall verbal information is essential for the long-term efficacy of psychoeducational programs and other psychological intervention to ensure the successful transfer of newly acquired skills or knowledge into everyday life. Aims of this study aimed to validate the MVALT among schizophrenia patients in HUSM. Methods: The subjects were 15 schizophrenia patients conveniently selected from the patients that attended follow up at the psychiatry clinic in HUSM or inpatients who have been admitted during the study period and 15 healthy control subjects as a comparison. Reliability and validity of the MVAVLT were analyzed. Results: The validation study showed that the Malay version Auditory Verbal Learning Test (MVAVLT) had a good validity (factor analysis 0.66 to 0.98) and test-retest reliability (pearson correlation ranged from 0.24 to 0.84) and has been shown to be sensitive in discriminating between normal and schizophrenia patients. In line with the previous research, the schizophrenia patients performed significantly worse than healthy control in all indexes measured in MVAVLT. Conclusion: The screening of deficits in verbal learning and memory among the schizophrenia patients is important, for early detection and treatment since it can be helpful for clinicians and psychologists in their counseling sessions. Subsequently, it helps patients to reduce such cognitive difficulties and their impact by using specific rehabilitation with the usage of newer antipsychotic agents.